Teenagers talking about reading and libraries. - Snowball, Clare (Australian Library and Information Association, 2008)
Past research has shown teenagers to be reluctant to read and less likely to visit libraries than younger children. These conclusions are debated and further investigation is needed. Difficulties abound in researching teenagers' opinions. Teenagers can be reluctant to participate in activities and peer support is often very important in determining their willingness to take part. Large-scale surveys of hundreds of student participants do not allow in-depth discussion of opinions and attitudes. Focus groups were conducted with metropolitan Perth high school students to investigate teenagers' thoughts on reading and libraries. Although some teenagers were enamoured of reading and libraries, others were more scathing but still found ways to take part in literacy activities and acquire the information they needed to negotiate their world.